AB0687 EFFECTIVENESS OF SPECIALIZED AND INTENSIVE ADL TRAINING IN PATIENTS WITH IDIOPATHIC INFLAMMATORY MYOPATHIES – PRELIMINARY RESULTS OF A ONE-YEAR CONTROLLED STUDY. (June 2019) - Špiritović, Maja; Oreska, Sabina; Štorkánová, Hana; Heřmánková, Barbora; Česák, Petr; Rathouská, Adéla; Kubinova, Kateřina; Klein, Martin; Vernerová, Lucia; Růžičková, Olga; Mann, Heřman; Pavelka, Karel; et al.
Abstract : Background: Idiopathic inflammatory myopathy are characterized by muscle weakness, caused by inflammation and immune changes in the affected muscles, which lead to a limitation in the execution of day-to-day activities (ADL). The aim of our study was to investigate the impact of specialized and intensive aDL training on muscle strength and endurance, depression and QoL of IIM patients. Objectives: The study included a total of 50 IIM patients who fulfilled the Bohan and Peter 1975 criteria and had skeletal muscle involvement. 27 patients were recruited into the intervention group (IG) and 23 patients into the control group (CG). Both groups received an educational material for home exercise, but only the IG underwent a 6-month intensive training with a subsequent 6-month follow-up period. Methods: Patients were assessed by a physician and a physiotherapist blinded to intervention at months 0, 3, 6, and 12. Patients also filled out patient reported outcomes questionnaires and provided blood for routine laboratory analysis and bio-banking. Data analysis was performed between groups and within the group. Results: Compared to the observed statistically significant deterioration in the CG over the intervention period, we found a statistically significant improvement in the IG in objectively assessed strength and endurance of muscles as well as in subjectively assessed functional abilities and depression (Table). During the follow-up period, there was a significant deterioration or stagnation of the achieved positive results in the IG. Nevertheless, improved functional ability during the intervention period persisted in the IG in the follow-up period as well. Only numerical improvements in the IG during the intervention compared to the numerical deterioration in CG, that did not reach statistical significance, were observed in some subjectively assessed domains of QoL (SF-36) and fatigue (FIS – in physical dimension). Conclusion: Our specialized and intensive aDL workout led to a significant improvement in the observed parameters that was clinically significant in a substantial proportion of patients, and prevention of the expected worsening of muscle weakness and QoL. Acknowledgement: Supported by aZV-16-33574A, SVV for FTVS UK 2019-260466, MHCR 023728. Disclosure of interests: Maja Špiritović: None declared, Sabina Oreska: None declared, Hana Štorkánová: None declared, Barbora Heřmánková: None declared, Petr Česák: None declared, adéla Rathouská: None declared, Kateřina Kubinova: None declared, Martin Klein: None declared, Lucia Vernerová: None declared, Olga Růžičková: None declared, Heřman Mann Consultant for: Pfizer, Eli Lilly, Sanofi, Speakers bureau: abbVie, Roche, Pfizer, MSD, Eli Lilly, Sanofi, Karel Pavelka: None declared, Ladislav Šenolt Grant/research support from: abbVie, Consultant for: abbVie, Bristol-Myers Squibb, Celgene Corporation, Merck Sharp and Dohme, Novartis, Pfizer, Roche, UCB, amgen, Takeda, Speakers bureau: abbVie, amgen, Bristol-Myers Squibb, Celgene Corporation, Eli Lilly, Merck Sharp and Dohme, Novartis, Pfizer, Roche, UCB, Jiří Vencovský Consultant for: Samsung, Speakers bureau: abbVie, Novartis, Pfizer, Sanofi, Eli Lilly, Biogen, UCB, MSD, Werfen, Roche, Michal Tomčík: None declared